Um modelo para a criminalidade no município de São Paulo em 2001 - Sartoris Neto, Alexandre [UNESP] (My University, 2011)
This work aims to estimate an empirical model for three kinds of crime in Sao Paulo city: homicides, robberies and car thefts. It uses as geographical units the areas belonging to each police districts and takes in account spatial effects among the variables. The results show important differences when we deal with crime against people and crime against property.

Esto trabajo búsqueda estudiar un modelo empírico para tres tipos de crimen en la ciudad de Sao Paulo: muertes, robos y hurto de automóviles. Las unidades geográficas son las regiones cerca de las centrales de policía y considera los efectos espaciales de interacción entre las variables. Los resultados muestran importantes diferencias en los crímenes que envuelven personas y propiedades.

Este trabalho tem como objetivo estimar um modelo empírico para três tipos de crime no município de São Paulo: homicídios, roubos e furto de veículos. O trabalho usa como unidades geográficas as áreas de atuação dos distritos policiais e leva em conta possíveis efeitos espaciais entre as variáveis. Os resultados mostram diferenças importantes quando tratamos com crimes contra a pessoa e contra a propriedade.
Keywords: Economics of crime; Spatial econometrics; Homicide; Robbery; Theft; Economía del crimen; Econometría especial; Muerte; Robo; Hurto; Economia do crime; Econometria espacial; Homicídio; Roubo; Furto